ORGANISING PERSONALISED LEARNING IN THE ENGLISH LANGUAGE CLASSROOM: COMPUTER ENGINEERING AND INFORMATION TECHNOLOGY UNDERGRADUATES PERSPECTIVES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The more rapidly the area of information technologies develops, the higher are the requirements for training Computer Engineering and Information Technology students. Computer Engineering and Information Technology students training should be aimed at equipping them with subject-specific knowledge, on the one hand, and skills of the 21st century including strong communication skills in English, on the other hand. As practice shows good communication skills in English may lead to better job opportunities, more stable and prosperous future. The desire to succeed in mastering communication skills in English is directly related to Computer Engineering and Information Technology students’ attitudes towards both English as a discipline and activities used in the English language classroom. Computer Engineering and Information Technology students show interest and enjoy learning only when it becomes personally meaningful to them. The research aim is to find out Computer Engineering and Information Technology undergraduates’ opinions on organising personalised learning in the English language classroom aimed at developing their communication skills. The researchers used a convenience sampling technique to select the research population. The research population comprised 273 Computer Engineering and Information Technology first and second year students from Kyiv National Economic University named after Vadym Hetman and Kyiv National University of Technologies and Design. To collect statistical data on Computer Engineering and Information Technology undergraduates’ opinions on organising personalised learning in the English language classroom the team of researchers developed a questionnaire and data collection took place in September-December 2023.